Enam Alasan Guru Menggunakan Metode Ceramah pada Mata Pelajaran PAI - Tri Sumarsih; Wirdati Wirdati (Prodi Pendidikan Keagamaan Islam, 2022)
Curriculum 13 requires the use of student-based methods. However, at SD Negeri 161/II Bukit Sari, it turns out that teachers tend to continue to use the lecture method. This study aims to determine the reason PAI teachers still use the lecture method, as one of the general methods in learning. The research method used is qualitative with a case study approach. To obtain data in the field which aims to describe and answer the problems being studied, and in the research process, the authors need to use data collection methods, namely the observation method by observation and the interview method consisting of Islamic religious education teachers, school principals, homerooms and students. To strengthen research data, researchers also take data through documentation. All interview data were analyzed by collecting data, reducing data, presenting data, and ending with the conclusion. The data validation technique was carried out by researchers using source triangulation, which was done by checking the data that had been obtained through several sources. The results of this study indicate that there are 6 reasons teachers still use the lecture method: First, the method used in schools is the lecture method combined with discussion, question and answer methods, and assignments. Second, this lecture method is an effective and easy method to apply. Third, the condition of the class during the learning process is conducive. Fourth, the facilities provided at the school are adequate, but if the student-based method is applied, it cannot run well because the media and other aids are not sufficient. Fifth, while using the lecture method students feel happy and easy to understand the material. Sixth, students' behavior and responses during the learning process are good.